The role of the Peruvian State in the fight against labor exploitation as a contemporary form of slavery: “La Malvinas” case - Rebaza Vilchez, Karen Maribel (2017)
This article provides a critical study- from a constitutional and international perspective- of the role of the peruvian State in the fight against labour exploitation,as a contemporary form of slavery, regarding the death of two Peruvian young people in the fire of the old Nicolini factory located in “Las Malvinas”commercial quarter